Potential Mechanism and Effects of Different Selenium Sources and Different Effective Microorganism Supplementation Levels on Growth Performance, Meat Quality, and Muscle Fiber Characteristics of Three-Yellow Chickens - Xue, Junjing; Fang, Chengkun; Mu, Rui; Zhuo, Ruiwen; Xiao, Yuanyuan; Qing, Yiqing; Tang, Jiaxi; Fang, Rejun (Frontiers in Nutrition, 2022)
A trial was conducted to investigate the effects of different Se sources including sodium selenite (S - Se) and selenium yeast (Y - Se) and different effective microorganism (EM) addition levels on growth performance, meat quality and muscle fiber characteristics of three - yellow chickens and its potential mechanism. A total of 400 birds were randomly distributed into 4 groups (S - Se, S - Se + EM, Y - Se, and Y - Se + EM groups) consisting of a 2 × 2 factorial arrangement. The main factors were the source of Se (ISe = inorganic Se: 0.2 mg/kg S - Se; OSe = organic Se: 0.2 mg/kg Y - Se) and the level of EM (HEMB = high EM: 0.5% EM; ZEMB = low EM: 0% EM). Each treatment had 5 replicates and each replicate consisted of 20 broiler chickens. The trial lasted for 70 days. The results showed that, in breast muscle, broiler chickens fed OSe source decreased the pH24h, drip loss, shear force, perimeter, cross - sectional area and diameter, but increased the a*24h and density compared with the broiler chickens fed ISe source (P < 0.05); Broiler chickens supplied with HEMB level decreased the cross - sectional area and diameter, but increased the pH24h, a*24h and density compared with the broiler chickens supplied with ZEMB level (P < 0.05). In thigh muscle, OSe source and HEMB level also could improve the meat quality and change muscle fiber characteristics of broiler chickens (P < 0.05). Meat quality was correlation with the muscle fiber characteristics (P < 0.05). OSe source and HEMB level could regulate the expression levels of muscle fiber - relative genes in the breast and thigh muscles (P < 0.05). In conclusion, OSe source and HEMB level could improve the meat quality of the breast and thigh muscles of three - yellow chickens through changing the muscle fiber characteristics, and they changed the muscle fiber characteristics by regulating the expression levels of muscle fiber - relative genes.